Random Scan Approach for Image Steganography - Gupta, Sahil; Garg, Kamal Deep (Asian Journal of Electrical Sciences, 2017)
Steganography is the art of hiding information in a cover media. The cover and secret data can take many forms such as text, audio, images and videos. In this paper, secret data in the form of (image) is hidden into the cover image. To achieve perceptual invisibility and Robustness, Random Scan approach is used. Before embedding data in cover media, an encryption technique is applied on secret data. Experimental results confirm the PSNR superiority of proposed algorithm.